Clonal varieties of Conilon coffee for the Espírito Santo State, Brazil - Bragança, Scheilla Marina; Carvalho, Carlos Henrique Siqueira de; Fonseca, Aymbiré Francisco Almeida da; Ferrão, Romário Gava (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to select and to multiply clones of Conilon coffee (Coffea canephora Pierre ex Froehner) to obtain clonal varieties with improved yield and quality. Two hundred and sixty seven mother plants were selected based on coffee grain yield, rust (Hemilea vastatrix) resistance, brown blight (Colletotrichum sp.) resistance, plant architecture, plant vigor, fruit size and time to fruit maturity. The selected clones were evaluated in four field experiments conducted on a Dark Yellow Latosol (Oxisol) at Instituto Capixaba de Pesquisa, Assistência Técnica e Extensão Rural (INCAPER), in Marilândia, ES, Brazil. Coffee trees were planted in rows 3.5 m apart with 1.5 m between plants in the rows. A randomized block design with four replications and six plants per plot was used. The selected clones, EMCAPA 8111, EMCAPA 8121, and EMCAPA 8131, early, medium and late maturity, respectively, were released for the State of Espírito Santo, Brazil. The productivity varied from 58 to 60 bags of 60 kg and was 33% greater than the control variety.